If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(5x+10)+10=6x-(x=10)
We move all terms to the left:
3(5x+10)+10-(6x-(x)=0
We multiply parentheses
15x-(6x-x+10+30=0
| 2a—4=8 | | -3x+5(x-6)=36 | | (6x−18)=(4x−8)=(4x−4) | | 6x-5=-14-3x | | 9x+2=7x+3 | | -18x-10=8 | | Xx14+23=65 | | x+(x+15)=125 | | -14x+12=12 | | -13x-6=-19 | | 7(2x+5)=9+2(8x+8) | | 19x+8=-11 | | 13x+3+5x+15=60 | | 7+30x=9 | | 7=30x=9 | | 4(2x-6)=86 | | 14=6n+6=2n | | 6x-5=14-3x | | 15+2m=31 | | x+16+13x+21=137 | | 2g+6285=5000 | | 13x+21+x+16=137 | | 2(y+7)=y-4 | | 4(7u+3)=12 | | X-0.2x=78.80 | | X-0.2x=78 | | x+79+x+81=142 | | 4b+7=9b+22 | | 4n^2+16n-6=0 | | 9=p−-6 | | 77=-10(x-7) | | -4(-t-1)=-20 |